Phase aspects of (broadband) stimulated Raman scattering - Offerhaus Herman L.; Garbacik Erik T.; van Rhijn Alexander C.W.; Fussell Andrew L.; Herek Jennifer L. (Reviews in Analytical Chemistry, 2012)
The phase of the molecular response can be exploited to improve selectivity without sacrificing speed in both narrowband and broadband coherent anti-Stokes Raman scattering (CARS) microscopy, both of which will be considered in this review of the work that was performed in our group.